Experimental design and multicriteria decision making methods for the optimization of ice cream composition - Rojas, Cristian (2012)
The aim of the present work was to optimize the sensorial and technological features of ice cream. The experimental work was performed in two stages: 1) optimization of lactose enzymatic hydrolysis, and 2) optimization of the process and product. For the first stage a complete factorial design was developed, optimized using both response surface and the steepest ascent method. In the second stage a mixture design was performed, combining the process variables. The product with the best sensorial acceptance, high yield and low cost was selected. The acceptance of the product was developed by an untrained taster’s panel. As a main result the sensorial and technological features of the final product were improved, establishing the optimum parameters for its elaboration.